2015
DOI: 10.1509/jppm.14.181
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Constraints and Entrepreneurial Intentions in Subsistence Marketplaces

Abstract: More than a billion entrepreneurs worldwide live in subsistence contexts and run microenterprises to meet life's basic consumption needs. In this article, the authors investigate how two types of consumption constraints in poverty, chronic and periodic constraints, combine to influence entrepreneurial intention. Chronic and periodic constraints are concomitant in subsistence marketplaces and represent consumption-side constraints. A field experiment shows that chronic constraints amplify entrepreneurial intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 59 publications
3
67
1
Order By: Relevance
“…This research highlights the need for a microlevel, situated, authentic understanding of QOL experiences in subsistence marketplaces, not only required for businesses (Viswanathan et al, 2009), but also for consumers, active subsistence marketplace agents, to deeply understand the sources of their own well-being. Acting in the capacity of "consumer-entrepreneurs" (Viswanathan et al, 2010;Venugopal et al, 2015), subaltern consumers turn to market-based storytelling to reorganize themselves around their own chronotopefication meanings and discover the positive in the face of negative/inhumane circumstances. Jagadale et al (2018) suggested creating marketing systems with political and economic controls in the hands of subaltern consumers.…”
Section: Consumer Affairs Implicationsmentioning
confidence: 99%
“…This research highlights the need for a microlevel, situated, authentic understanding of QOL experiences in subsistence marketplaces, not only required for businesses (Viswanathan et al, 2009), but also for consumers, active subsistence marketplace agents, to deeply understand the sources of their own well-being. Acting in the capacity of "consumer-entrepreneurs" (Viswanathan et al, 2010;Venugopal et al, 2015), subaltern consumers turn to market-based storytelling to reorganize themselves around their own chronotopefication meanings and discover the positive in the face of negative/inhumane circumstances. Jagadale et al (2018) suggested creating marketing systems with political and economic controls in the hands of subaltern consumers.…”
Section: Consumer Affairs Implicationsmentioning
confidence: 99%
“…We have also examined what individuals living in extreme scarcity sustain, bottom-up, such as surviving, relating (to others and the environment), and growing (for themselves or the next generation; Viswanathan et al 2014). This stream of research has also examined chronic versus periodic consumption constraints or resource scarcity (Venugopal, Viswanathan, and Jung 2015). Chronic extreme scarcity can also have variations such as during the end of the month or during different stages of the agricultural cycle, which are periodic in nature.…”
Section: Functional Literacy In the Marketplacementioning
confidence: 99%
“…For example, one subset of consumer research seeks concrete solutions to its alleviation without fully noting its parameters. Utilizing various methodologies, consumer researchers discover answers to questions such as how circumstances among the poor can be improved by entrepreneurial activities (Venugopal, Viswanathan, and Jung 2015), how access to credit and rural banking systems support or fail to support their needs (Dadzie et al 2013), and how income and food security are related to use of food pantries and food stamps in low-income households (Bhattarai, Duffy, and Raymond 2005). Researchers develop general frameworks that can be used broadly, such as work developed by Scott et al (2011), who examined social justice in the global marketplace, and by Martin and Hill (2012), who developed the consumption adequacy benchmark via a worldwide analysis.…”
Section: Consumer Well-being and Public Policy Researchmentioning
confidence: 99%